The Power of Profanity: How Female Stand-Up Comedians Use Swear Words - Ummil, Khairah; Latifah, Nur (CV. Kalimasada Group Profesional, 2024)
Swearing is a sociolinguistic phenomenon that is very often found in everyday life. It is not only found in real life, but swearing is very easy to get in cyberspace, especially in the entertainment industry. This study focuses on sociolinguistic analysis which discusses cursing or swearing in one of the entertainment industries, namely Stand-Up Comedy which is used by female comic artists. The subject of this research is a female comic artist of Vietnamese, Chinese and American descent named Ali Wong. Ali Wong was used in this study because she brings up social issues which are quite sensitive such gender role such us motherhood and marriage, she used to swear in front of the audience as an expression of her personal social problems. The purpose of this study is to find out the types of swearing used by Ali Wong, then from these types this study tries to examine how Ali uttered the swearing words. This study uses a qualitative descriptive method, especially in observation and note-taking techniques. The data taken is data from Ali Wong's video collection on the Netflix platform, namely Ali Wong: Don Wong (2022) based on Ljung's theory (2011) which explains swearing words specifically and detail about swearing words. The collection process found approximately 33 swear words uttered by Ali Wong from the selected videos. This type of slot filler is the type that appears most often with an emphasis function that occupies the part level that is most widely used, such as fuck, shit.